2019
DOI: 10.18689/mjnn-1000132
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Materials as Catalyst support for Wastewater Treatment

Abstract: The scarcity of water resources has stimulated the exploration of sewage treatment technique. On account of flexible separation and recycling, heterogeneous catalysis has aroused strong interest among researchers. In terms of the specific surface area, pore dimension and catalytic sites distribution, porous materials hold infinite potentials in heterogeneous catalysis. Among different porous materials, mesoporous material is most favorable in aqueous system. Moderate diffusion flux and highly efficient mass tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…This is because GCN-500 is highly mesoporous, which is rich in active sites. It was found that the mesoporous property is also good in organic adsorption [ 42 ] and this helps to promote better photocatalytic performance. This is because once the pollutant adsorbs on the photocatalyst surface, photocatalysis can only take place.…”
Section: Resultsmentioning
confidence: 99%
“…This is because GCN-500 is highly mesoporous, which is rich in active sites. It was found that the mesoporous property is also good in organic adsorption [ 42 ] and this helps to promote better photocatalytic performance. This is because once the pollutant adsorbs on the photocatalyst surface, photocatalysis can only take place.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, supports drastically affect the catalytic properties of supported nanoparticles. Mesoporous materials with a large surface area used as catalyst supports make a critical difference to a better dispersion of active phase, preventing the particles aggregation, and, therefore, can improve the activity and reusability of the catalysts 8,9 . Interaction with the support material can also considerably affect the activity and selectivity of noble metals nanoparticles in various reactions including hydrogenation 10,11 …”
Section: Introductionmentioning
confidence: 99%